2012
DOI: 10.3892/or.2012.2210
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling pathway regulates human pancreatic cancer cell proliferation and metastasis

Abstract: Abstract. Pancreatic cancer is one of the most aggressive and devastating malignancies. The Hedgehog (Hh) pathway has been reported to play an important role in pancreatic cancer development and progression. The aim of this study was to examine the activation of the Hh pathway in human pancreatic cancer tissue samples and pancreatic cancer cell lines, and the molecular mechanisms involved in the Hh pathway mediated effects on pancreatic cancer cell proliferation and invasion. The expression levels of Hh molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 45 publications
1
37
0
Order By: Relevance
“…The present study posed and verified the hypothesis that the hedgehog signaling pathway activates the PI3K/AKT pathway, which subsequently upregulates the expression of MMP-2 and MMP-9 at the mRNA and protein level, thereby mediating GBM migration and invasion. The hedgehog signaling pathway has a vital role in the control of cell differentiation, cell proliferation and embryonic development (5,7,12). According to recent studies, aberrant activation of hedgehog signaling is linked to the aggressiveness of multiple tumor types, including GBM (21,22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study posed and verified the hypothesis that the hedgehog signaling pathway activates the PI3K/AKT pathway, which subsequently upregulates the expression of MMP-2 and MMP-9 at the mRNA and protein level, thereby mediating GBM migration and invasion. The hedgehog signaling pathway has a vital role in the control of cell differentiation, cell proliferation and embryonic development (5,7,12). According to recent studies, aberrant activation of hedgehog signaling is linked to the aggressiveness of multiple tumor types, including GBM (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…The hedgehog signaling pathway is essential for embryonic patterning and cancer development (5)(6)(7). The hedgehog protein family includes desert hedgehog, Indian hedgehog and sonic hedgehog (SHH).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies showed that Shh signaling can activate pancreatic stellate cells, promotes fibroblast infiltration, and increases secretion of fibronectin, collagen type I, MMPs, and TGF-β [62]. Studies in the pancreatic cancer cell line PANC-1 showed that inhibition of Hedgehog signaling by Smoothened (Smo) suppression can reverse EMT, induce apoptosis via PI3K/AKT inhibition, and inhibit the invasion of pancreatic cancer cells [63]. Moreover, combination of focal irradiation with Hedgehog signaling inhibition reduces lymph node metastasis in an orthotopic animal model [64].…”
Section: Regulatory Pathways In Pancreatic Cancer Stem Cellsmentioning
confidence: 99%
“…Despite research efforts, there has been limited progress regarding the treatment of this disease; therefore, novel strategies to identify new therapeutic agents are urgently required. The Hedgehog (Hh) signaling pathway is critical for morphogenesis signaling and is inappropriately activated in patients with pancreatic cancer (2,3). In addition, this pathway is associated with the growth and metastasis of various types of tumors, including pancreatic cancer (4,5).…”
Section: Introductionmentioning
confidence: 99%